UNILATERAL BARTHOLIN’S GLAND CYST IN A DOG - JAYAKUMAR, C; C.M, SUDHA; E, NIYAZ; R H, NAVEENKUMAR (The Indian Journal of Animal Reproduction, 2016)
A rare case of unilateral bartholin’s gland cyst causing tenesmus in a dog was diagnosed. The cyst was drained and vaginal wall was sutured leading to uneventful recovery.